The Impact of Decision Investment, Capital Structure and Growth on Profitability and Company Value in Manufacturing Sector of Firms in Indonesia - Hikma Niar (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
Purpose of this study is to analyze investment decisions, profitability, capital structure, company growth and firm value population 149 manufacturing companies with 55 samples. Used Analysis Path. The results of the study show that the results of this study are expected to contribute to the development of financial management studies. Keywords: Investment Decision, Capital Structure, Growth, Profitability and Corporate Value